Music Performance Anxiety: Can Expressive Writing Intervention Help? - Tang, Yiqing; Ryan, Lee (Frontiers in Psychology, 2020)
Performance is an essential part of music education; however, many music professionals and students suffer from music performance anxiety (MPA). The purpose of this study was to investigate whether a 10-minute expressive writing intervention (EWI) can effectively reduce performance anxiety and improve overall performance outcomes in college-level piano students. Two groups of music students (16 piano major students and 19 group/secondary piano students) participated in the study. Piano major students performed a solo work from memory, while group/secondary piano students took a sight-reading exam of an eight-measure piano musical selection. All students performed twice, at baseline and post-EWI, with two or three days between performances. During the EWI phase, students were randomly divided into two groups: an expressive writing group and a control group. Students in the expressive writing group wrote down feelings and thoughts about their upcoming performances, while students in the control group wrote about a topic unrelated to performing. Each student’s pulse was recorded immediately before performing, and each performance was videotaped. Three independent judges evaluated the recordings using a modified version of the Observational Scale for Piano Practicing (OSPP) by Gruson (1988). The results revealed that, by simply writing out their thoughts and feelings right before performing, students who had high MPA improved their performance quality significantly and reduced their MPA significantly. Our findings suggest that EWI may be a viable tool to alleviate music performance anxiety.